Dulaan a documentary on the Philippine theater - Tiongson, Nicanor (Tuklas sining series, 1989)
Features the varied and colorful traditions that shaped theater in the Philippines. These include indigenous rituals and dances; the Spanish-influenced komedya, sinakulo, sarsuela and drama; the American-influenced bodabil and modern "legitimate" plays; and the realistic and expressionistic plays of today.